Studies toward the total synthesis of microsclerodermin G - Burnett, Cameron Moeller, author; Williams, Robert Michael, advisor; Kennan, Alan J., committee member; Rovis, Tomislav, 1968-, committee member; Bernstein, E. R. (Elliot R.), committee member; Belisle, John Theodore, committee member (Colorado State University. Libraries, 2010)
We report our studies toward the synthesis of microsclerodermin G, a cyclic hexapeptide with antifungal and antitumor activity. The dehydrotryptophan amino acid was synthesized according to literature precedents. (3R)-γ-amino-β-hydroxybutyric acid (GABOB) was synthesized according to previous methodology from our research group. An aspartate-based precursor to the pyrrolidinone moiety of microsclerodermin G was prepared in four steps from known materials. 3-amino-6-methyl-12-phenyl-2,4,5-trihydroxydodeca-7,9,11-trienoic acid (AMPTD) was prepared in seven steps from known materials; the synthesis utilized Evans' chiral oxazolidinone glycolate aldol reaction and the sulfinimine-based Mannich reaction developed by Ellman. Syntheses of two dipeptides are reported, as are other attempts at coupling of the various amino acids.
Department Head: Ellen R. Fisher.
Keywords: synthesis; AMPTD; microsclerodermin G; organic; Macrocyclic compounds -- Synthesis; Peptides -- Synthesis; Amino acids -- Synthesis